Spill-over effects of monetary policy: a progress report on interest rate convergence in Europe - Michael Fladung (Deutsche Bundesbank, 2007)
This study examines differences in the interest rate response to an ECB policy impulse in the euro area, the new EU-member states, and in the other non-eurozone EU countries in order to gauge the degree of interest rate alignment in Europe. To this end, PANIC, a Panel Analysis of Non-stationarity in I diosyncratic and Common components, is employed in a structural factor set-up. Under the assumption that the ECB sets the short end of the yield curve, the analysis shows that : (i) The response of Europe's money and government bond markets to new information can be summarized by two common stochastic trends and one stationary common factor, which together explain more than 68% of the overall variation of the two market segments; (ii) one of the factor innovations can be associated with the ECB's policy stance, which strongly affects the short end of the euro area's yield curve; (iii) compared to the euro area, the short-term market segments in the new EU-member states react, on average, 12% more weakly to the monetary policy signal, whereas these countries' long-term government bond yields respond up to 25% more strongly to such a common innovation.
Keywords: E52; G15; C33; 330; Factor Models; Common Stochastic Trends; Interest Rate Channel; New Member States; Mixed Data Sampling; Geldpolitik; Zinsparität; Spillover-Effekt; EU-Staaten; EU-Staaten (Osteuropa)